1998
DOI: 10.1007/s000180050183
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte integrins and inflammation

Abstract: Leukocyte adhesion is of pivotal functional importance. Without adequate adhesion, T lymphocytes and natural killer cells are not cytotoxic, B cells cannot develop into antibody secreting plasma cells, leukocytes do not home into inflamed tissues and myeloid cells are not able to phagocytize or exhibit chemotactic responses. During evolution several leukocyte adhesion molecules have developed belonging to a few molecular families. Among these, the leukocyte-specific integrins (beta 2 integrins, CD11/CD18 molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
81
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 50 publications
2
81
0
1
Order By: Relevance
“…Conversely, CD11b is implicated in various adhesive interactions of myeloid cells (macrophages, monocytes, and granulocytes) (Ji, 2012) and belongs to a family of integrins (Arnaout, 1990). It is found also on natural killer (NK) cells and certain subpopulations of B lymphocytes (Flotte et al 1983;Gahmberg et al, 1998;Liu et al, 2004;Solovjov et al, 2005), but not on dendritic cells. The macrophage population represents the complexity of various phenotypes during embryonic development (Leenen et al, 1994); however, since this marker is often utilized for detection of embryonic macrophages, we can posit that these scattered cells bearing CD11b or/and F4/80 markers of embryonic heart are macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, CD11b is implicated in various adhesive interactions of myeloid cells (macrophages, monocytes, and granulocytes) (Ji, 2012) and belongs to a family of integrins (Arnaout, 1990). It is found also on natural killer (NK) cells and certain subpopulations of B lymphocytes (Flotte et al 1983;Gahmberg et al, 1998;Liu et al, 2004;Solovjov et al, 2005), but not on dendritic cells. The macrophage population represents the complexity of various phenotypes during embryonic development (Leenen et al, 1994); however, since this marker is often utilized for detection of embryonic macrophages, we can posit that these scattered cells bearing CD11b or/and F4/80 markers of embryonic heart are macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The pivotal role of these integrins for the immune response is documented by the finding that individuals lacking b2-integrins (leukocyte-adhesion deficiency syndrome I) develop severe, life-threatening, bacterial and fungal infections (reviewed in [8]). Previously, we have shown that the human Thy-1 (CD90) is an activation-associated cell-adhesion molecule, which is involved in the adhesion of neutrophils to activated microvascular EC via the interaction with the b2-leukocyte integrin Mac-1 (CD11b/ CD18) [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The integrin LFA-1 (lymphocyte function-associated antigen-1, also known as CD11a/CD18 or ␣ L ␤ 2 ) is a member of the leukocyte (␤2) subfamily of integrins that is expressed on the cell surface of all leukocytes (4,5). This molecule mediates important adhesive phenomena through interactions with its ligands intercellular adhesion molecules (ICAM-1, 1 -2, or -3).…”
mentioning
confidence: 99%